2015
DOI: 10.2105/ajph.2014.302249
|View full text |Cite
|
Sign up to set email alerts
|

Recall of Anti-Tobacco Advertisements and Effects on Quitting Behavior: Results From the California Smokers Cohort

Abstract: IntroductionEvidence indicates that anti-tobacco advertisement can be an effective way of encouraging smokers to quit smoking, but the majority of this evidence uses aggregate measures of assessing advertisement exposure rather than exposure to specific advertisements. ObjectiveUsing a sample of California Adults (18-64 years) (n = 2596), we sought to assess recall of four anti-tobacco television advertisements developed by the California Tobacco Control Program (CTCP) and assess how recall of each advertiseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…35,36 Specifically for tobacco, Leas et al reported that better recall of anti-tobacco video ads predicted smoking cessation at follow-up. 37 By experimentally demonstrating that emotionally salient graphic component of GWLs enhance the memorability of warning messages, the present study provides an insight about the features of an effective GWL. However, our findings do not directly link the messages' memorability and their effectiveness at reducing smoking.…”
Section: Discussionmentioning
confidence: 72%
“…35,36 Specifically for tobacco, Leas et al reported that better recall of anti-tobacco video ads predicted smoking cessation at follow-up. 37 By experimentally demonstrating that emotionally salient graphic component of GWLs enhance the memorability of warning messages, the present study provides an insight about the features of an effective GWL. However, our findings do not directly link the messages' memorability and their effectiveness at reducing smoking.…”
Section: Discussionmentioning
confidence: 72%
“…This example suggests frequently changed advertisements for poorly known and graphic risks may evoke more searches. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Blake et al (2015) did not find an association between information exposure and e-cigarette addiction beliefs among current US adult cigarette smokers [22]. We thought based on the empirical and theoretical literature noting that media could affect beliefs and behaviors [31, 48, 54], as well as the media campaigns [3335, 5556] focused on tobacco product harms that media exposure would be associated with addiction beliefs. The diverse media landscape makes it challenging to identify an association between general media exposure and specific beliefs, like addiction beliefs.…”
Section: Discussionmentioning
confidence: 98%